RANCANGAN ALAT BANTU PENETAS TELUR OTOMATIS KAPASITAS 100 TELUR - Putri Endah Suwarni; Riski Aditia (Industrika : Jurnal Ilmiah Teknik Industri, 2023)
Egg incubators are needed by chicken farmers, helping the production process in hatching chicken eggs. From observations made by some farmers in Lampung, they still use manual incubators, giving rise to complaints for breeders. Had to turn the eggs over, measure the humidity even constrained when the heating light suddenly went out. With this, an automatic egg incubator will be designed which has a capacity of 100 eggs. In the design process using the Autocad application. The results of the design have an image scale of 1:10. With a size where the length is 95cm, width 50cm, height 40cm. With internal components there are indicator lights, heating elements, thermohygrostat, time delay relay, thermohygrostat switch, time delay relay switch, indicator light switch, top egg rack, bottom egg rack, water container, heating element 2, dynamo actuator 1, dynamo actuator 2.